2016
DOI: 10.1016/j.juro.2016.06.095
|View full text |Cite
|
Sign up to set email alerts
|

A Whole Blood Assay for AR-V7 and ARv567esin Patients with Prostate Cancer

Abstract: Purpose The majority of prostate cancer mortality can be attributed to metastatic castration-resistant prostate cancer, an advanced stage which remains incurable despite recent advances. The androgen receptor (AR) signaling axis remains active in CRPC. Recent studies suggest that the expression of an AR splice variant, AR-V7, may underlie resistance to abiraterone and enzalutamide. However, controversy exists over the optimal assay. The objective of this study is to develop a fast and sensitive assay for AR sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 29 publications
2
59
0
Order By: Relevance
“…Further studies revealed its expression mostly related to late-stage mCRPC, whereas expression in primary tumor was low or even absent (8,12,14,23,29). Recently, AR-V567es expression has been detected in liquid biopsy samples of patients with prostate cancer (13,22,24). However, there have been conflicting results regarding the incidence of AR-V567es, that is, a range of patients with AR-V567espositive mCRPC from 3% (14) up to over 70% (13,15,24).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies revealed its expression mostly related to late-stage mCRPC, whereas expression in primary tumor was low or even absent (8,12,14,23,29). Recently, AR-V567es expression has been detected in liquid biopsy samples of patients with prostate cancer (13,22,24). However, there have been conflicting results regarding the incidence of AR-V567es, that is, a range of patients with AR-V567espositive mCRPC from 3% (14) up to over 70% (13,15,24).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have linked AR alternative splicing, particularly AR-V7, to the development of enzalutamide, abiraterone and docetaxel resistance (21, 29, 42). Clinical studies suggest that AR-V7 in circulating tumor cells from patients with CRPC is associated with resistance to enzalutamide and abiraterone (22, 43). Several pre-clinical studies revealed that AR variants might play certain roles in taxane resistance which could be through blocking nuclear translocation via AR.…”
Section: Discussionmentioning
confidence: 99%
“…In a seminal study, Antonarakis and coworkers showed that men with detectable expression of AR-V7 mRNA in CTCs had reduced response rates to enzalutamide and abiraterone (Antonarakis et al 2014). More recent work has revealed that AR-V7 transcript is also detectable in whole blood (Liu et al 2016) and predicts poor response to abiraterone (Todenhofer et al 2016). The predictive value of AR-V7 is not limited to transcript expression as a recently developed CTC-based immunofluorescence assay demonstrated that nuclear expression of AR-V7 predicts worse survival after treatment with AR-targeted therapies (Scher et al 2016).…”
Section: Ar Splice Variantsmentioning
confidence: 99%